Micellar Effects on Nucleophilic Addition Reaction and Applicability of Enzyme Catalysis Model - R. K. London Singh (E-Journal of Chemistry)
This study describes the effect of anionic and cationic micelles on nucleophilic addition reaction of rosaniline hydrochloride (RH) with hydroxide under pseudo-first order condition. Strong inhibitory effect is observed due to SDS micelle, whereas CTAB catalysed the reaction. This is explained on the basis of electrostatic and hydrophobic interactions which are simultaneously operating in the reaction system. The kinetic data obtained is quantitatively analysed by applying the positive cooperativity model of enzyme catalysis. Binding constants and influence of counterions on the reaction have also been investigated.